The Effect of Cooperative Learning Model and Discipline on History Learning Achievement - Nora Asmirna; Riyanto; Eko Risdianto (Indonesian Journal of Pedagogy and Teacher Education, 2024)
The study aims to ascertain three things: (1) the difference in learning achievement in history between students using the Jigsaw cooperative learning model and students using the Studen Teams Achievement Divisions (STAD) model; (2) the impact of high and low discipline on learning achievement; and (3) the possibility of an interaction between cooperative learning models and discipline on history learning achievement. This study employed experimental research as its research methodology. The 2023–2024 academic year saw the conducting of this study at SMAN 11 North Bengkulu and SMAN 13 North Bengkulu. The XI social studies classes made up the study's population. Two groups were chosen at random to serve as research samples: one was the treatment group, which I taught using Jigsaw-style instruction, and the other used Studen Teams Achievement Divisions (STAD) instruction. This study employed a 2x2 factorial ANOVA research design. The application of Jigsaw and Studen Teams Achievement Divisions (STAD) has an impact on student learning achievement. High and low discipline have an impact on history learning achievement. Cooperative learning models and discipline have an impact on history learning achievement. These are the study's findings.